1. The problem statement, all variables and given/known data Solve ln(sinh-1(x)) = 1 (Just give the formula for x, no calculator is necessary) sinh-1(x) = asinh 2. Relevant equations 3. The attempt at a solution When I did this, I knew sinh-1(x) = ln(x + sqrt.(x^2 +1), but the equation would look like ln(ln(x + sqrt.(x^2 + 1 )) = 1, which looks weird because I don't what to do afterwards So then I tried exponentiate both sides and it will be asinh(x) = e then multiplying both sides by sinh, so my answer is x = sinhe, is this right?